The Internet as a Glocal Discourse Environment -- A Commentary on Lam and Bloch - Dimitris Koutsogiannis; Bessie Mitsikopoulou (Language Learning and Technology)
The Internet as a worldwide literacy practice environment has created a new situation in communication, providing a new dynamic field for research. On the basis of the two articles under discussion, this commentary develops three main aspects of the Internet: as an informal learning environment for English as a second/foreign language; as a discursive space where identities are formed and social relationships are negotiated; and, as a space where the intermingling of the global and the local gives rise to hybrid language varieties. Taking into account that electronic environments are not neutral literacy practice environments but are involved in a complex nexus of power structures and relations that also need to be explored, this paper briefly addresses issues related to theoretical and methodological approaches for the study of language varieties in the Internet.